Continuous-flow photochemistry as an automated platform integrated with closed-loop AI/ML approaches - Pijper, Brenda (2023)
In this Activity article, Brenda Pijper (Horizon 2020 PhotoReAct early-stage researcher in the Chemical Technologies group at Janssen, the Pharmaceutical Companies of Johnson & Johnson) and Jesus Alcázar (head of the Chemical Technologies group at Janssen) and Gabriela Oksdath-Mansilla and Fabricio R. Bisogno (both professors at the Universidad Nacional de Córdoba and researchers at the National Scientific and Technical Research Council of Argentina [CONICET]) discuss the current state of continuous-flow photochemistry in drug discovery and its future as an automated platform integrated with closed-loop artificial intelligence and machine learning (AI/ML) approaches.